Anxiety and Depression Leads To Death Instinct in Entwistle’s and Hall’s I am not Okay with This - Amelia, Dea; Hidayat, Syarif; Sulaeman, Karina A.; Hariyana, Agustinus (BRIGHT : A Journal of English Language Teaching, Linguistics and Literature, 2024)
This study aims to analyze a movie script from the Netflix series entitled I am Not Okay With This written by Jonathan Entwistle and Christy Hall which was adapted from a comic book by Charles Forsman with the same title. This study focuses on discussing the psychological aspects experienced by Sydney Novak as the main character. This study uses a qualitative approach and is presented with a descriptive method. The data collection techniques used include literature review, observation, and note-taking method. The object of the research used is the I am Not Okay With This movie script through an intrinsic approach in the form of characterization, plot, and setting, then linking it with an extrinsic approach using Sigmund Freud's theory of anxiety, life and death instinct and the theory of psychotic depression. This study is also supported by reviewing books, journals, and other research sources from the internet as secondary data references. The results obtained from this study are that it is known that the supernatural powers experienced by Syd are a manifestation of the anxiety she has suffered from the grief since the death of her father. This anxiety is also related to the appearance of hallucinations that lead to the death instinct in Syd’s actions and behaviors.